Independent Curriculum In Early Children's Education - Farantika, Dessy; Rachmah, Laela Lutfiana; Setyowati, Rina Insani; Sanjaya, Maulinda Sulistyani (Annual Conference on Islamic Early Childhood Education (ACIECE), 2023)
This research was motivated by the start of the curriculum independence for driving schools at every level of education, including early childhood education. The independent curriculum is a new curriculum, and compiling a new curriculum is not easy for every educational unit. This is a polemic that is often felt by PAUD educators and their managers every time the curriculum changes. However, the independent curriculum is not yet mandatory for every early childhood education institution. There are three alternative options for implementation. It is important to carry out this research to provide an understanding of the essence and method of preparing an independent curriculum. This type of research is literature study research where the researcher examines and analyzes various theories and existing regulations related to the concept of an independent curriculum and how it is structured in early childhood education units. The research results show that the independent curriculum aligns with the concept of independent learning launched by the Minister of Education and Culture. When preparing an independent curriculum, what needs to be considered is the curriculum's basic framework and structure. National Education Standards as a reference and framework that has been translated into curriculum structure, learning principles, and assessment and learning outcomes. In the independent curriculum, the curriculum structure contains intracurricular activities to strengthen the profile of Pancasila students.